Controlled Smart Anisotropic Unidirectional Spreading of Droplet on a Fibrous Surface. (21st July 2015) - Zhang, Miaoxin; Wang, Lei; Hou, Yongping; Shi, Weiwei; Feng, Shile; Zheng, Yongmei
<x xml:space="preserve">Abstract</x> Smart anisotropic‐unidirectional spreading is displayed on a wettable‐gradient‐aligned fibrous surface due to a synergetic directing effect from the aligned structure and the ratio of hydrophilic components.